Recurrent hypoglycaemia in type 2 diabetic patient due to hypothyroidism - Kumar, Alok (J Diabetes Metab Disord, 2015)
OBJECTIVE: To present a case report of recurrent hypoglycaemia in type 2 diabetic patient due to hypothyroidism. METHODS: We describe a case with type 2 diabetes who complained of episodes of recurrent hypoglycaemia in last few weeks. We also discuss the results of the diagnostic workup done to find out the cause of recurrent hypoglycaemia. RESULT: After ruling out common causes like overdosing of oral hypoglycaemic agents or insulin, renal or hepatic impairment we found overt hypothyroidism as a cause of recurrent hypoglycaemia. Levothyroxine therapy was started in this patient. Upon normalization of thyroid function, patient did not further experience any episodes of hypoglycaemia. We did not find any report on hypothyroidism as a cause of recurrent hypoglycaemia in type 2 diabetic patients. CONCLUSION: We conclude that during workup, clinicians should take hypothyroidism into consideration as a potential cause of hypoglycaemia in type 2 diabetic patients.